Legal Aspects of Radiography and Radiology. - Dimond, Bridgit C. (John Wiley & Sons, 2008)
Practical and jargon-free, this book is aimed at the non-lawyer and includes an extensive glossary of terms. It emphasises the legal issues encountered by those working in diagnostic radiography, radiotherapy and radiology and includes examples of legal dilemmas taken from these disciplines as well as exploring current issues.